The Influence of the Habitual Curriculum in Islamic Religious Education (PAI) on the Noble Character of Junior High School Students - Aqmal agustiansyah; Iwan Hermawan; Nia Karnia (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to evaluate the implementation of the habitual curriculum in Islamic Religious Education (PAI), assess the level of students’ akhlak karimah, and analyze the effect of the habitual curriculum on akhlak karimah among eighth-grade students at SMP Negeri 7 Karawang Barat. This study addresses a research gap, namely the limited empirical evidence regarding the direct contribution of the habitual curriculum to the development of akhlak karimah at the junior high school level. The research employed a quantitative correlational approach, with the population comprising all eighth-grade students, and data were collected using validated questionnaires. Data analysis included normality and linearity tests, followed by simple linear regression using IBM SPSS Statistics. The results indicate that the implementation of the habitual curriculum falls into the moderate category (mean = 94.27), while students’ akhlak karimah is also moderate (mean = 83.19). Simple linear regression analysis showed a significance value of 0.326 (>0.05) and a coefficient of determination of 1.6%, indicating that the habitual curriculum does not have a significant effect on students’ akhlak karimah. These findings suggest that most of the variation in akhlak karimah is influenced by external factors such as parenting, social environment, teacher role modeling, and school culture. The novelty of this study lies in the empirical evaluation of the habitual curriculum’s effect on students’ akhlak karimah in the context of PAI, which has been rarely explored. The findings contribute significantly to the literature on character education and provide insights for developing more effective moral habituation strategies in secondary schools.